UZBEK LITERATURE OF THE 20TH CENTURY - Aslbek Khamzaugli Ergashev (Galaxy International Interdisciplinary Research Journal, 2023)
The development of literature in Uzbekistan continues today. Uzbek writers continue to create new works that reflect the life, customs and traditions of their country. Uzbek literature continues to attract the attention of readers and remain an important element of the cultural heritage of the country and its peoples.